Ecologic and Sociodemographic Risk Determinants for Dengue Transmission in Urban Areas in Thailand - Koyadun, Surachart; Butraporn, Piyarat; Kittayapong, Pattamaporn (Interdisciplinary Perspectives on Infectious Diseases, 2012)
This study analyzed the association between household-level ecologic and individual-level sociodemographic determinants and dengue transmission in urban areas of Chachoengsao province, Thailand. The ecologic and sociodemographic variables were examined by univariate analysis and multivariate logistic regression. In the ecologic model, dengue risk was related to households situated in the ecotope of residential mixed with commercial and densely populated urban residential areas (RCDENPURA) (aOR = 2.23, P=0.009), high historical dengue risk area (aOR = 2.06, P<0.001), and presence of household window screens (aOR = 1.62, P=0.023). In the sociodemographic model, the dengue risk was related to householders aged >45 years (aOR = 3.24, P=0.003), secondary and higher educational degrees (aOR = 2.33, P=0.013), household members >4 persons (aOR = 2.01, P=0.02), and community effort in environmental management by clean-up campaign (aOR = 1.91, P=0.035). It is possible that the preventive measures were positively correlated with dengue risk because these activities were generally carried out in particular households or communities following dengue experiences or dengue outbreaks. Interestingly, the ecotope of RCDENPURA and high historical dengue risk area appeared to be very good predictors of dengue incidences.